Content validity test on moss plant e-book media with Aiken formula - Abdullah Muamar; Amin Retnoningsih; Yustinus Ulung Anggraito (Journal of Science Education Research, 2021)
Plantae material consists of three primary materials, namely moss, ferns, and seed plants. Moss plant material is difficult for students to understand. Hence, It is necessary to develop an e-book on moss plants that can provide learning solutions related to moss plant material. This study aims to measure the level of validity, feasibility assessment by High-School Biology Subject Teacher Forum (STF) in Semarang City, and student readability. The research and development method used is the 4-D development model. Several stages in the development research are define, design, develop and disseminate. The development stage includes expert validation, feasibility, and student readability tests. The research subjects are students of class X SMA N 12 Semarang. The data collection instruments are expert validation sheets, assessment sheets, and readability sheets. The analysis technique used is descriptive data analysis. The result of the e-book validity test for the material content, presentation, and language assessment aspects are 96% (very good), 96% (very good), and 94% (very good), respectively. The results of the assessment by learning media experts is 93% (very good). The e-book feasibility test by STF in Semarang is 95% (very good), and the e-book readability test is 90% (strongly agree).